The Cat Fur Mite, Lynxacarus radovskyi Tenorio, 1974 (Acarina: Astigmata: Listrophoridae) from Cat, Felis catus in Peninsular Malaysia - Jeffery, J.; Norhidayu, S.; Mohd Zain, S.N.; Noor Hayati, M.I.; Nurazila, B. (2012)
The cat fur mite, Lynxacarus radovskyi Tenorio, 1974 (Acarina: Astigmata: Listrophoridae) is reported from cats, Felis catus from three sites in peninsular Malaysia. The first site is a Malay village, Kampong Menteri in Taiping, Perak, where the mites were found on local pet cats. The other two sites are urban cities of Kuala Lumpur, in the Federal Territory and Georgetown, in the island of Penang. Mites from the urban areas were collected from stray cats. Although several ectoparasites (fleas, mites, ticks and lice) have been previously reported, L. radovskyi is recorded herein for the first time on cats from peninsular Malaysia.